Anionic Amphiphilic Cyclodextrins Bearing Oleic Grafts for the Stabilization of Ruthenium Nanoparticles Efficient in Aqueous Catalytic Hydrogenation. Issue 4 (19th December 2019) - Cocq, Aurélien; Léger, Bastien; Noël, Sébastien; Bricout, Hervé; Djedaïni‐Pilard, Florence; Tilloy, Sébastien; Monflier, Eric
Abstract: Oleic succinyl β‐cyclodextrin was proved to be efficient for the stabilization of ruthenium nanoparticles (NPs) in aqueous medium. These NPs were characterized by FTIR spectroscopy and transition electron microscopy (TEM). The catalytic activity of these NPs was evaluated in the aqueous hydrogenation of petrosourced and biosourced unsaturated compounds such as benzene and furfural derivatives. The catalytic system can be easily recycled and reused up to nine runs without any loss of activity and selectivity, demonstrating its robustness. Abstract : Metallic nanoparticles and cyclodextrin : Ruthenium nanoparticles (NPs) are stabilized by oleic succinyl‐β‐cyclodextrin in water. These NPs were efficient in the aqueous hydrogenation of petrosourced and biosourced substrates. The catalytic system can be easily recycled and reused up to nine runs.